2021
DOI: 10.3389/fmed.2021.744958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Position Change From the Bed to a Wheelchair on the Regional Ventilation Distribution Assessed by Electrical Impedance Tomography in Patients With Respiratory Failure

Abstract: Background: There is limited knowledge about the effect of position change on regional lung ventilation in patients with respiratory failure. This study aimed to examine the physiological alteration of regional lung ventilation during the position change from lying in bed to sitting on a wheelchair.Methods: In this study, 41 patients with respiratory failure who were weaned from the ventilators were prospectively enrolled. The electrical impedance tomography (EIT) was used to assess the regional lung ventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This novel imaging technology allows real-time non-invasive monitoring of ventilation distribution (Zhao et al, 2020). Two recent studies applying EIT to monitor lung aeration before, during and after physiotherapy showed similar findings that physiotherapy improved ventilation distribution (Longhini et al, 2020;Yuan et al, 2021). Together we have a better understanding why early physiotherapy can improve lung functions.…”
Section: Editorial On the Research Topicmentioning
confidence: 80%
“…This novel imaging technology allows real-time non-invasive monitoring of ventilation distribution (Zhao et al, 2020). Two recent studies applying EIT to monitor lung aeration before, during and after physiotherapy showed similar findings that physiotherapy improved ventilation distribution (Longhini et al, 2020;Yuan et al, 2021). Together we have a better understanding why early physiotherapy can improve lung functions.…”
Section: Editorial On the Research Topicmentioning
confidence: 80%
“…The position of diaphragm differs at various upper body positions, which influences the lung volume [ 12 ]. The postural effects may improve lung function of ICU patients, as suggested in previous studies with EIT [ 13 , 14 ]. In these studies, EIT-derived parameters between supine and sitting positions were compared.…”
Section: Introductionmentioning
confidence: 78%
“…Since the lung regions became smaller and ventilation distributed towards dorsal part, the GI slightly increased in tilted positions. In general, gravity-dependent diaphragm displacement influenced the regional ventilation distribution and therefore, could be used on ICU patients for early rehabilitations [ 13 , 14 ]. In addition, the heart descended towards abdomen during the position change from supine to sitting.…”
Section: Discussionmentioning
confidence: 99%
“…Postural therapy has been widely accepted in critically ill patients to support ventilation redistribution towards the dependent lung areas, thus facilitating recruitment [101].…”
Section: Posturementioning
confidence: 99%